SOVIET SOCIAL SECURITY MODEL’S FUNCTIONS, DEVELOPMENT AND LITHUANIA - GUOGIS, ARVYDAS; BOGDANOVA, NATALIJA (Politologija, 2012)
This article is unique in that, for the first time, Russian and Soviet social security development in Lithuania is studied comprehensively and systematically including all major types of social insurance, tracking changes over time and identify their causes. The article broadly analyzes the social security legislation, the publications of Soviet Union’s and Lithuanian SSR’s official statistics, presents national and international analysis and the archival materials, revealing how the Lithuanian social security system evolved during Russian and Soviet rule. The article reveals the structure and ideology of the Soviet social insurance system. In the whole territory of the USSR, the same principles and laws of social insurance were applied. The foundations for Soviet social security and social insurance systems were layed rather early – already 8–10 years before the II world war began. But Soviet Union, especially after 1940, was not totally homogeneous. In several Soviet republics, for example Lithuania, some specific elements were observed which influenced the administrative methods in social security, social insurance and social support. The article explains the nature of social insurance expenditure. We define and explain the branches of social insurance in the USSR: old age and disability pensions, illness, maternity, funeral and unemployment benefits (the latter were paid in the early Soviet period only). The article deals with official USSR and Lithuanian SSR statistics, mainly from the last Soviet period (beginning 1975), when Soviet social insurance reached its limits and showed its potential. Although Soviet social insurance was related to the principles of the Bismarckian work record and former earnings, it was however financed from Moscow’s centrally organised budget and was not related to meaningful contributions of employers and employees. The one-party communist system had a big role in the functioning of social insurance in the USSR and the Lithuanian SSR. The article shows that the Lithuanian social protection system because of the occupation of Russia (1795–1914) and the Soviet Union (1940–1990) was closely related to the system of pre-revolution Russian and Soviet Union’s, with some insignificant regional differences. The social security programs were used as instruments to strengthen workers’ control. No other country in the world but USSR has used its social security system as a tool for propaganda. Despite that, the Soviet Union and the Lithuanian SSR did not stay aloof from social security system reforms in the world. When Lithuania was occupied by the Soviet Union in 1940, it had to comply with the formed system of social insurance and social care. The main role in Lithuanian SSR was given to the social insurance scheme, which did not involve contributions of the residents (instead, it was done by work organizations, and administered by the state and trade unions). In comparison with other soviet republics, Lithuania featured a higher level of independence in the social care field than in the field of social insurance, and the Lithuanian authorities used it wisely to build nursing homes for elderly and improving their administration, supporting children of poor families, etc. However, certain economic-social conditions in Lithuania also had an effect on the social insurance, e.g. there were more working old-age pensioners in Lithuania, and social insurance was administered more effectively than in the rest of the USSR republics. Notably, social security specialists from other USSR republics were coming to Lithuania to gather good practice.